PENINGKATAN KREATIVITAS MUSIK DALAM BERNYANYI MELALUI MEDIA INSTRUMEN MUSIK - SALINA, DERI (PPs UNJ, 2011)
The purpose of the research is to understanding music creativity improvement in singing, concerning music study through the use of music instrument. Based on implications from research findings, the teachers should be careful in selecting music teaching methods which is approriate to improve the music creativity in singing student. Therefore, it is recommended to elementary school teachers mastering one of music instrument as that method that could improve musical cerativity, optimally.Keywords: creativity, music, instrument